2014
DOI: 10.1007/s10973-014-3963-4
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetry in testing waste materials from the brown coal combustion

Abstract: The calorimetric measurements were applied in testing the wastes collected from different furnaces in electric power plants as materials to be used in civil engineering. The fly ash materials were collected from two power stations based on different brown coal deposits and working with conventional and fluidized bed installation. The reactivity of high calcium fly ash from sub-bituminous coal combustion has been proved in calorimetric, conductometric, chemical shrinkage, and rheological measurements before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…Addition of fly ash more distinctly retards the acceleratory period of cement hydration than slag, this tendency is especially clear for the high substitution rate of fly ashes. This retarding effect of the mineral additions on the cement hydration has been already reported [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Addition of fly ash more distinctly retards the acceleratory period of cement hydration than slag, this tendency is especially clear for the high substitution rate of fly ashes. This retarding effect of the mineral additions on the cement hydration has been already reported [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultssupporting
confidence: 67%
“…For composite binders containing fly ash, the hydration heat evolution has been studied, inter alia, by Nocuń-Wczelik [25][26][27], Pacewska et al [28][29][30], Giergiczny [31,32], Han et al [22], Kumar et al [33], Narmluk et al [34] and Mounanga et al [35]. Similarly, as for slag cements, the tests showed that the evolved heat decreases with increasing amount of fly ash addition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of fly ashes originating from fluidized bed combustion in cement applications has been investigated in several studies (Li et al 2012;Nocuń-Wczelik et al 2014;Pavoine et al 2014;Rajamma et al 2009Rajamma et al , 2015Roszczynialski and Nocuń-Wczelik 2004;Sinsiri et al 2010;Wu et al 2014;Zhao et al 2015). Most of these studies are focused on fly ash from coal combustion and only few (Rajamma et al 2009(Rajamma et al , 2015 on biomass fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the cement-waste expanded perlite mixtures were produced. The kinetics of hydration was evaluated with the help of calorimetric method; this method appeared many times as a best way to obtain basic information dealing with the hydraulic activity of many binders of different origin [7][8][9]. There are some data dealing with the kinetics of heat evolution in cement-natural perlite systems [2], as well as in the waste expanded perlite-cement systems [3].…”
Section: Introductionmentioning
confidence: 99%